2014
DOI: 10.1007/s10273-014-1705-7
|View full text |Cite
|
Sign up to set email alerts
|

Ist die Energiewende sozial gerecht?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 0 publications
0
15
0
6
Order By: Relevance
“…Other studies examine specific policies, such as the long-term impact of an emissions trading scheme in Australia 45 , the existing broad set of environmental taxes in Denmark 21 , the consequences of the EU energy package for Finland 46 , or renewable energy subsidies in Germany [47][48][49][50][51] . Similarly as in the case of carbon taxation, regressive distributional effects are reported in the studies and revenue recycling is found to be able to mitigate these effects.…”
Section: The Case Of Developed Countriesmentioning
confidence: 99%
“…Other studies examine specific policies, such as the long-term impact of an emissions trading scheme in Australia 45 , the existing broad set of environmental taxes in Denmark 21 , the consequences of the EU energy package for Finland 46 , or renewable energy subsidies in Germany [47][48][49][50][51] . Similarly as in the case of carbon taxation, regressive distributional effects are reported in the studies and revenue recycling is found to be able to mitigate these effects.…”
Section: The Case Of Developed Countriesmentioning
confidence: 99%
“…Hierdurch entstehen erhebliche Kosten, die von den Stromverbrauchern zu tragen sind. Diese Kosten sind seit dem Jahr 2000, in dem das Erneuerbare-Energien-Gesetz Vielmehr spielt auch eine wichtige Rolle, dass von Strompreissteigerungen einkommensschwache Haushalte verhältnismäßig stärker betroffen sind als einkommensstarke Haushalte (Bardt und Niehues, 2013;Grösche und Schröder, 2014;Heindl et al, 2014).…”
Section: Introductionunclassified
“…Social justice was a founding principle of sustainable development (WCED 1987) and recent empirical research has proven the appreciation people in different countries show for an equitable approach to climate policy (Schleich et al 2014). In addition, current energy transformation debates have raised questions on a fair burden sharing, especially because even an efficient policy mix is expected to increase overall costs (Heindl et al 2014).…”
Section: Introductionmentioning
confidence: 99%